A "Far North Dixie Land": Black Settlement, Discrimination, and Community in Urban Alaska. Issue 1 (15th November 2019) - Hartman, Ian C; Reamer, David
Abstract: Though it never ranked among the top destinations of the Great Migration, Alaska nevertheless enticed thousands of African Americans during the postwar decades. On the one hand, Black Alaskans experienced the lamentable patterns that defined American race relations in the twentieth century: housing and job discrimination alongside marginalization and racial violence. On the other hand, Black men and women also found in Alaska a place to make their own. This article presents a case study of urban history in the American West and demonstrates that despite its distance from other metropolitan centers, Alaska's largest city, Anchorage, was not excluded from major postwar trends. Rather, many of the defining through-lines of midcentury U.S. history—mass migration, racial discrimination, community formation, urban planning, and civic activism, to name a few—were present and comprise a dynamic story that until now has never been told.